Model Luxury Brand dalam Menciptakan Purchase Intention - Ramadyanti, Mustika; Wibowo, Lili Adi; Purnama, Ridwan (Business Education Program of Universitas Pendidikan Indonesia, 2019)
This research aims to determine the Effect of Luxury Brand on Purchase Intention iPhone X on member of the Indonesian iDevice Community. Type of this research is descriptive verification. Dependent variable of this research is purchase intention (Y), and luxury brand (X) as independent variable. The population are member of the Indonesian iDevice Community. This research uses a simple random sampling method and probability sampling techniques to 200 member. Data analysis technique using Structural Equation Modeling (SEM) with IBM SPSS AMOS version 24.0 for Windows. The findings of this research indicates that luxury brand and purchase intention are in good category. Luxury brand has a positive and significant influence on purchase intention. Extended self which is one of luxury brand’s dimension gives the biggest contribution of purchase intention building.